2015
DOI: 10.4328/jcam.2317
|View full text |Cite
|
Sign up to set email alerts
|

Learning Styles, Academic Achievement, and Gender in a Medical School Setting

Abstract: ÖzetAmaç: Çalışmada klinik öncesi dönemdeki tıp öğrencilerinin öğrenme stilleri, cinsiyet ve akademik başarıları arasındaki ilişkinin değerlendirilmesi amaç-lanmıştır. Gereç ve Yöntem: Fakültemizdeki tüm klinik öncesi dönem tıp öğ-rencileri çalışmaya alınmıştır. Öğrenme stillerini belirlemek için öğrenme stillerini altı kategoride (bağımsız, bağımlı, rekabetçi, işbirlikçi, çekingen ve katılımcı) inceleyen Grasha -Reichmann Öğrenme Stilleri Ölçeği kullanılmış-tır. Öğrencilerin akademik başarıları kurul sınav pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
(15 reference statements)
1
7
0
Order By: Relevance
“…Besides the above described ‘peer effect’ and the role of motivation, students’ interpersonal relationships, such as help-seeking relationships, fellow students’ support, and friendship, also may influence students’ academic performance [ 21 , 45 , 46 ]. It is known that the dynamic and degree of closeness of students’ interpersonal relationships predicts similarity in academic achievement to some extent [ 21 , 47 , 48 ]. It is possible that students in mixed international LCs feel more relatedness with their peers in the same LC and are more eager to make a connection with each other for not only study-related support but also for friendship networks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the above described ‘peer effect’ and the role of motivation, students’ interpersonal relationships, such as help-seeking relationships, fellow students’ support, and friendship, also may influence students’ academic performance [ 21 , 45 , 46 ]. It is known that the dynamic and degree of closeness of students’ interpersonal relationships predicts similarity in academic achievement to some extent [ 21 , 47 , 48 ]. It is possible that students in mixed international LCs feel more relatedness with their peers in the same LC and are more eager to make a connection with each other for not only study-related support but also for friendship networks.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is worthwhile to know how students' social networks develop and compare that among different group compositions [47]. Next to the formal learning network as organized by the faculty, the informal learning network may also crucially influence students' academic achievement [51].…”
Section: Strengths and Limitations Of The Study Further Research Andmentioning
confidence: 99%
“…This is supported by recent data demonstrating a correlation between primary learning style and gender in the medical school setting. [ 29 ]…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the predominantly female nature of both student cohorts skewed the overall learning style preference towards the dependent category, especially in 2015. However, this may not be problematic, as Kulac et al [21] found that female medical students preferring the dependent style scored higher than their male counterparts in examinations. Unpopularity of the avoidant and competitive categories was seen across all genders in both cohorts, which could be considered a similarity between gender preferences.…”
Section: Researchmentioning
confidence: 99%